ANALISA ERROR PADA KETERAMPILAN MENULIS MAHASISWA SEMESTER DUA FAKULTAS EKONOMI MANAJEMEN UNIVERSITAS ISLAM BATIK SURAKATA TAHUN AJARAN 2011/2012 - Dosen Fakultas Ekonomi Universitas Islam Batik Surakarta, Eny Kustiyah, Ariviani Dewi (MAJALAH ILMIAH GEMA, 2012)
The objectives of the research are (1) to reveal the type of error in Economic Management Students of Batik Islamic University of Surakarta in the second semester, (2) to get to know the role of error in second language learning. The method of the research is descriptive qualitative. The sources of data are derived from the students’ thematic composition, books, scientific journals, and virtual sources. While the type of data are text consist of words, phrases, clauses, and sentences. The present researcher uses note taking to collect the data. The use of error analysis theory will help for a comprehensible understanding. This study has examined the types of error in Economic Management students of Batik Islamic University in the second semester. Whereas the types of error in this study are omission, addition, misformation, and misordering. It has also discoverd the source of error whether interference, intralingual or development error. This study finds the significant  role of error in the second language learning by giving remedial lesson.  The finding moves further that error analysis becomes the bridge of the relationship between teacher and student.The study has also discovered that error analysis becomes part of language learning evaluation.     Key words: error, omission, addition, misformation, misordering, interference, intralingual, the role of error